Europejskie poświadczenie spadkowe jako podstawa wpisu do polskiej księgi wieczystej - Borzemska, Kaja (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Regulation No 650/2012 of the European Parliament and of the Council of 4 July 2012 was passed to harmonize the conflicting regulations of succession law in the Member States of the European Union. It came into effect on August 16, 2012, in all EU Member States with the exception of Denmark, Ireland and the United Kingdom. The Regulation introduced the European Certificate of Succession, regulated in Articles 62–73 of Chapter VI. At the time of its issuance, the European Certificate of Succession is valid in every EU Member State without applying any special procedures. This means that no authority presented with the Certificate issued by another Member State is entitled to request that a decision, an authentic instrument, or court settlement be presented in its stead. According to Article 69(5), the Certificate shall constitute a valid document for the recording of succession property in the relevant register of a Member State. Refusal to recognize the Certificate as a valid and effective document by the authorities of a Member State would be considered a blatant breach of EU law
Keywords: europejskie poświadczenie spadkowe; unijne rozporządzenie spadkowe; księgi wieczyste; prawo właściwe; jurysdykcja